Using model texts as a type of feedback in EFL writing - Wu, Zhixin; Qie, Jiaxin; Wang, Xuehua (Frontiers in Psychology, 2023)
Recent work has established that model texts could be employed as a useful feedback technique. However, few studies have employed argumentative writing tasks and analyzed draft quality, and little is known about the role played by the language analytic ability in using model texts. The current study aimed to investigate what Chinese EFL learners (n = 60) noticed at the composition and comparison (comparing their texts with model texts) processes in a four-stage argumentative writing task and explore to what degree model texts can enhance the learners’ subsequent writing. The four stages were: (1) writing (pre-test); (2) comparing (treatment); (3) rewriting (immediate post-test); (4) delayed writing (delayed post-test). The findings showed that learners primarily noticed lexical features in the composition and comparison stages. Higher language analytic ability (LAA) learners and guided noticing learners could notice and elicit more information from the model texts. Overall, the use of model texts was effective in improving learners’ writing by providing alternative elements associated with lexis, grammar, content, and organization. In addition, the beneficial effect of model texts on writing could be maintained after 1 week. Some pedagogical implications are put forward to help teachers make better use of model texts to improve learners’ writing. This study also provides new insights into how language analytic ability affects the effectiveness of using models and provides more information on the type of learner most likely to benefit from model texts.